Cardiovascular disease risk reduction in diabetes through conventional and natural approaches. Issue 4 (December 2017) - Schultz, William M.; Mahlof, Elliot N.; Dhindsa, Devinder S.; Varghese, Tina; Heinl, Robert E.; Cai, Hannah C.; Sandesara, Pratik B.; Eapen, Danny J.; Sperling, Laurence S.
Abstract : Type 2 diabetes mellitus (DM) is a significant cause of premature complications and mortality in patients with cardiovascular disease (CVD). In addition to lifestyle modifications, conventional treatment of DM consists of oral hypoglycemic agents, insulin sensitizers, and subcutaneous insulin. In diabetic individuals with or at risk for CVD, aspirin and statin therapy reduce CVD morbidity and mortality. Several natural or herbal supplements have shown potential benefit in patients with CVD and DM. We provide an overview of the current guidelines for treatment of DM and CVD. We then review the literature to describe the efficacy of natural approaches to CVD risk reduction in diabetic patients, with a focus on physical activity, dietary modification, and natural/herbal supplements. Activity and diet improve cardiovascular outcomes in patients with CVD and DM. Natural and herbal supplements have potential for benefit but require further research to determine their efficacy and safety.